2017
DOI: 10.1016/j.cell.2017.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM Reveals How Human Cytoplasmic Dynein Is Auto-inhibited and Activated

Abstract: SummaryCytoplasmic dynein-1 binds dynactin and cargo adaptor proteins to form a transport machine capable of long-distance processive movement along microtubules. However, it is unclear why dynein-1 moves poorly on its own or how it is activated by dynactin. Here, we present a cryoelectron microscopy structure of the complete 1.4-megadalton human dynein-1 complex in an inhibited state known as the phi-particle. We reveal the 3D structure of the cargo binding dynein tail and show how self-dimerization of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
523
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(559 citation statements)
references
References 58 publications
36
523
0
Order By: Relevance
“…In the cases of R241L and N283R, the gain-offunctions observed in vitro are possibly causative of the in vivo deficiencies, indicating that a faster or more processive motor is not advantageous for the spindle positioning function (see Discussion regarding K1475Q). This is consistent with recent studies that showed gain-of-functions in dynein (or dynein regulators) can lead to defects in dyneinmediated neuronal maturation 85 , or spindle orientation 72 .…”
Section: Single Molecule Motility Assays Reveal Insight Into Dynein-isupporting
confidence: 93%
See 1 more Smart Citation
“…In the cases of R241L and N283R, the gain-offunctions observed in vitro are possibly causative of the in vivo deficiencies, indicating that a faster or more processive motor is not advantageous for the spindle positioning function (see Discussion regarding K1475Q). This is consistent with recent studies that showed gain-of-functions in dynein (or dynein regulators) can lead to defects in dyneinmediated neuronal maturation 85 , or spindle orientation 72 .…”
Section: Single Molecule Motility Assays Reveal Insight Into Dynein-isupporting
confidence: 93%
“…5D) -which would result in fewer motor complexes being engaged for a spindle movement event -is the basis for cellular dysfunction. Given the auto-inhibited Phi particle exhibits reduced affinity for dynactin 72 , the altered localization pattern of the mutant may be due to disruption of a similar autoinhibitory conformation in yeast, consequent increased dynactin binding, and thus an increase in the frequency of cortical off-loading events 63 . Previous studies have suggested that dynein's interaction with dynactin is a limiting step in the delivery of dynein-dynactin complexes to cortical Num1 sites 77 .…”
Section: Discussionmentioning
confidence: 99%
“…4j). These include the human COPI complex (7 subunits, 558 kDa) (Wang et al, 2016), cytoplasmic Dynein complex (12 subunits, 1380 kDa) (Zhang et al, 2017), CSN complex (8 subunits, 343 kDa) (Mosadeghi et al, 2016) and SCF complex (5 subunits, 180 kDa) (Zheng et al, 2002). The recombinant COPI complex sample has been used to study the structure of coatomer in its soluble form (Wang et al, 2016).…”
Section: Multiprotein Complexes Expressed Using Smartbac Systemmentioning
confidence: 99%
“…Structural studies of canonical cytoplasmic dynein and the dynein that powers retrograde intraflagellar transport revealed an auto‐inhibited state (the φ particle), in which two motor heads stack together forming an interface that buries the linkers that cross the AAA ring and in which the microtubule‐binding stalks are crossed, thus structurally inhibiting the main mechanical elements (Torisawa et al, ; Pigino & King, ; Toropova et al, ; Zhang et al, ). This structure is not observed in axonemal dyneins in situ, and thus the inhibited axonemal dynein state seen by Lin and Nicastro () has a distinct structural basis.…”
Section: Controling Dynein State Transitions To Generate Bendsmentioning
confidence: 99%